Biopolymer-Metal Complex Wool-Pd: An Efficient and Reusable Heterogeneous Catalyst for the Heck Cross-Coupling Reactions and Aerobic Oxidation of Alcohols in Aqueous Media - Wu, Shang; Zhang, Hong; Wang, Yanbin; Su, Qiong; Lei, Ziqiang; Wu, Lan (Letters in Organic Chemistry, 2014)
Heterogeneous palladium catalysts, which are supported by biopolymer, have been applied in water-mediated Heck and the oxidation of alcohols cyclic reaction without assistance of any phosphine ligands. More importantly, owing to the interconversion between the Pd0 and PdII oxidation states during the Heck and oxidation reaction course, the catalyst exhibits good activity in Heck cross-coupling reaction of bromobenzene with styrene and oxidation reaction of alcohols to corresponding aldehydes or ketones without overoxidation using air as the source of molecular oxygen. This heterogeneous wool-Pd catalyst is stable, shows negligible metal leaching, and can be reused several times in reactions without significant loss of activity and selectivity.
Keywords: wool-Pd complex